Komitmen Organisasi Untuk Meningkatkan Kinerja Pegawai Pada Organisasi Perangkat Daerah Di Pemerintah Kota Serang - Ues Alkurni, Mohammad; Prahiawan, Wawan; Kambara, Roni (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2020)
Quality human resources are an important factor to increase the productivity of government agencies. High competence is required to be able to support the improvement of employee performance achievements. The purpose of this study was to determine the effect of intellectual competence and work discipline on employee performance through organizational commitment as an intervening variable. The study population was an employee of planning, evaluation and organizational financial reporting analysts within the scope of the Serang City government with a total sample of 60 people. The data analysis technique used a structural equation model that was processed with the SmartPLS application. The results of the study prove that there is a significant influence with the direction of a positive relationship of intellectual competence on employee performance. There is no effect of intellectual competence on organizational commitment. There is a significant influence with the direction of the positive relationship of work discipline on organizational commitment. There is a significant influence with the direction of a positive relationship of work discipline on employee performance. There is a significant influence with the direction of a positive relationship of organizational commitment to employee performance.